ANALISIS TERHADAP IMPLEMENTASI KEBIJAKAN PENGELOLAAN JALAN DI KABUPATEN BANYUMAS - Sri Hartini; Setiajeng Kadarsih (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Basically, the management of roads expected to be able to meet the needs of safe, convenient, and efficient for transportation of goods and services. But in reality, the road management policy in the regional autonomy were still did not meet expectations. Based on the research, the policy of road management in Banyumas are roads construction and road maintenance program. Road construction are conducted to increasing and widening of roads and paving, while road maintenance are done through regular maintenance and periodic maintenance. Factors that influence the policy are legal substance that have not been set as a whole regarding the management of roads, law enforcement which still have its main office in the policyled, facility factor that were not optimal, the society that tend to release responsibility to the government, and permissive factors. Key words: policy, road management and legal factors